2014
DOI: 10.1186/1472-6890-14-21
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of HbA1c and lipids measured with dried blood spot versus venous samples: a systematic review and meta-analysis

Abstract: BackgroundLevels of haemoglobin A1c (HbA1c) and blood lipids are important determinants of risk in patients with diabetes. Standard analysis methods based upon venous blood samples can be logistically challenging in resource-poor settings where much of the diabetes epidemic is occurring. Dried blood spots (DBS) provide a simple alternative method for sample collection but the comparability of data from analyses based on DBS is not well established.MethodsWe conducted a systematic review and meta-analysis to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…TC concentrations from the DBS method and venous blood samples measured by two accredited laboratories correlated strongly (Vitas and Fürst; Spearman r = .94, P < .001 for both). In a meta‐analysis based on 12 studies, a close agreement between HbA1c measured by DBS and venous blood samples was found …”
Section: Methodssupporting
confidence: 92%
“…TC concentrations from the DBS method and venous blood samples measured by two accredited laboratories correlated strongly (Vitas and Fürst; Spearman r = .94, P < .001 for both). In a meta‐analysis based on 12 studies, a close agreement between HbA1c measured by DBS and venous blood samples was found …”
Section: Methodssupporting
confidence: 92%
“…In addition, the CHS relied on analysis of dried blood spots to assess total cholesterol and HbA1c whereas the NHANES used venous blood specimens. Although a growing body of research shows evidence of good concordance between methods 22 and the dried blood spot testing is becoming widely-used in large scale, population-based survey research 40 , analysis of venous blood remains the “gold standard.” Concerns regarding reliance on dried blood spot testing in the CHS may be somewhat mitigated given that self-reports and the physical assessments for conditions not involving dried blood spot testing (i.e., hypertension) resulted in a similar pattern of findings.…”
Section: Discussionmentioning
confidence: 99%
“…DBS analysis for HbA1c has been validated against venous blood assays in several studies with venous blood scores predicting DBS scores with a high degree of accuracy. 22 A widely-used conversion formula was applied to equate DBS values to venous blood equivalent values. 23 For the CHS study, total cholesterol was measured using fluorometric assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis was done by immunoturbidimetry using the Randox latex agglutination inhibition assay (Randox Laboratories, Crumlin, UK). The DBS findings were minimally adjusted using a regression equation that defines the association between immunoturbidimetric analyses of HbA1c DBS samples and fasting venous samples tested using hand‐held glucose monitors . Diabetes was defined as self‐reported diabetes or HbA1c >6.5% and prediabetes as 5.7% < HbA1c ≤ 6.4%…”
Section: Methodsmentioning
confidence: 99%